SUMBANGAN SYEIKH MUHAMMAD ARSHAD B. ABDULLAH AL-BANJARI DALAM FIQH AL-AT‘IMAH (MAKANAN) DI DALAM KITAB SABIL AL-MUHTADIN (Syeikh Muhammad Arshad b. Abdullah al-Banjari’s Contribution of Fiqh of Foods in Sabil al-Muhtadin) - Ramli, Mohd Anuar; Jamaludin, Mohd Aizat (Journal of Al-Tamaddun, 2012)
Foods are basics needed for human being. It helps for physically growth, securing mental health and enhancing spiritual development. Islamic law stresses on consuming halal food and strictly forbids the non-halal as it affects the development of Muslim personality. This restriction is concerned and explained both by classical and contemporary Muslim scholars. Thus, this research focuses on contribution of Syeikh Muhammad Arshad al-Banjari in his writing of Book of Sabil al-Muhtadun, in which he had discussed in depth regarding issue of ?halal? aquatic animals, non-halal of two nature animals, ?Istitobah? (tasting), process of ?Istibra? (quarantine or seclusion) to ?al-Jallalah? animals etc. Furthermore, several research methods of books of fiqh as well as brief biography of the scholar are discussed and examined. Hence, this paper attempts to discuss the thought of Syeikh Arshad al-Banjari specifically in area of Fiqh al-At?imah (Fiqh of food).